A Copy Number Variant on Chromosome 20q13.3 Implicated in Thinness and Severe Obesity. (31st December 2015) - Hasstedt, Sandra J.; Xin, Yuanpei; Mao, Rong; Lewis, Tracey; Adams, Ted D.; Hunt, Steven C.
Abstract : Background/Objectives. To identify copy number variants (CNVs) which are associated with body mass index (BMI). Subjects/Methods. CNVs were identified using array comparative genomic hybridization (aCGH) on members of pedigrees ascertained through severely obese (BMI ≥ 35 kg/m 2 ) sib pairs (86 pedigrees) and thin (BMI ≤ 23 kg/m 2 ) probands (3 pedigrees). Association was inferred through pleiotropy of BMI with CNVlog ⁡ 2 intensity ratio. Results. A 77-kilobase CNV on chromosome 20q13.3, confirmed by real-time qPCR, exhibited deletions in the obese subjects and duplications in the thin subjects (P = 2.2 × 10 - 6 ). Further support for the presence of a deletion derived from inference by likelihood analysis of null alleles for SNPs residing in the region. Conclusions. One or more of 7 genes residing in a chromosome 20q13.3 CNV region appears to influence BMI. The strongest candidate is ARFRP1, which affects glucose metabolism in mice.